Pengaruh Jenis Aditif terhadap Mutu Fisik Ransum Berbahan Utama Rumput Raja (Pennisetum purpureoides) - Maria Selfiana Pasi; Maria magdalena kapitan; Oktovianus Rafael Nahak; Stefanus Sio; Agustinus Agung Dethan; Josua Sahala; Yasinta Sarifona Pasul (Tropical Livestock Science Journal, 2026)
This research investigated the impact of different additives on the physical quality of king grass-based complete silage (Pennisetum purpureoides). This study was carried out at the Laboratory of the Faculty of Agriculture, Science, and Health, University of Timor, during the period of July–August 2023. A Completely Randomized Design (CRD) was employed, consisting of treatments with replications each. The treatments included: P0 as the control (100 % king grass without additives), P1 (70% king grass + 20% rice bran + 5% Gliricidia sepium leaves + 5% sugar), P2 (70% king grass + 20% corn flour + 5% Gliricidia sepium leaves + 5% sugar), and P3 (70% king grass + 20% soybean meal + 5% Gliricidia sepium leaves + 5% sugar). The percentages of additional ingredients were calculated based on the weight of the main materials, consisting of chopped king grass and Gliricidia leaves. The parameters analyzed included color, aroma, texture, and mold presence assessed through sensory evaluation, while pH measurements were conducted using a pH meter. The percentage of mold contamination was determined by comparing the weight of the moldy portion of the silage to the total silage weight. The results indicated that the addition of additives had a significant effect (p<0.05) on the color, aroma, pH, texture, and mold development of the silage. Overall, the soybean meal treatment produced the best performance, as it effectively inhibited mold growth and generated a more desirable silage aroma compared to the control, rice bran, and corn flour treatments.